Ulta nagr k moto shah - Shazia, iftikhar (Ferozesons; pakistan, 2009)
"Ulta Nagr Ki Moto Shah" is a compelling and symbolic tale that explores the complexities of life, power, and identity, using vivid imagery and rich narrative to reflect on the contrast between appearance and reality.